JUAL BELI BARANG BEKAS MELALUI BANK SAMPAH PERSPEKTIF HUKUM ISLAM - Zarul Arifin (P3M dan Jurusan Syariah dan Ekonomi Bisnis Islam STAIN Sultan Abdurrahman Kepulauan Riau, 2021)
This research was conducted to explain the practice of selling used goods through a waste bank. This study aims to clearly illustrate the practice of buying and selling used goods through garbage banks in Sajad District and a review of Islamic law on buying and selling used goods through garbage banks in Sajad District . Based on the results of the study concluded that the practice of buying and selling used goods through a garbage bank in Sajad Subdistrict already meets the terms and conditions of sale and purchase and is carried out on a like and like basis and no party feels disadvantaged. Review of sharia economic law on the sale and purchase of used goods through waste banks including legal buying and selling because in terms of purity of used goods sold in garbage banks are sacred goods and for used goods in accordance with the opinion of Hanafiyah scholars allow the sale and purchase of goods affected by unclean not to eaten. In terms of prices in the sale and purchase of used goods there has been an agreement between the two parties and no one is harmed.